Strategi Pengembangan Usahatani Stevia di Desa Kolongan Atas Dua Kecamatan Sonder Kabupaten Minahasa - Yeheskel, Yeheskel; Rumagit, Grace Adonia Josephine; Mandei, Juliana Ruth (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This study aims to determine alternative strategies for developing stevia farming in Kolongan Atas Dua Village, Sonder District. The data collection method used was the survey method, which took primary and secondary data. The respondents were taken from farmer group members who cultivate stevia plants and stevia plant stakeholders, including the extension workers and the government. The data analysis method used in this research is a descriptive qualitative analysis using SWOT analysis. The results of this study indicate that alternative strategies for developing stevia farming in Kolongan Atas Dua Village, Sonder District, are (1) Utilizing land, suitable agro-climatic conditions, and adequate land area for the development of stevia farming and maximizing the use of privately owned land to meet the demand for stevia leaves. (2) Utilizing experience and improving farming skills to create superior products in the market. (3) Maximize using seeds from their breeding to increase production and establish cooperation with other parties/agencies for processing stevia leaves.